(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2024)
The article explores the factors that are attracting increasing attention to the protection of personal data and identifies the risks involved. In the era of digital progress and the widespread use of personal data in various spheres of life, privacy has become an important issue. The authors of the article analyzed the reasons why personal data protection has become a priority, including the rise in cybercrime, data breaches and privacy breaches. The article also discusses the risks associated with inadequate protection of personal data, including financial loss, reputational damage and privacy breaches.